STRATEGI BANK SYARIAH DALAM MEMAKSIMALKAN PERTAMBAHAN NASABAH DI KOTA PAREPARE - A. Haerunnisah Azizah; Nurhidayatullah Rahma; Rahman Ambo Masse (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
This article was written to provide an overview of sharia banking strategies in maximizing customer growth. comparing Islamic banks with commercial banks and the development of Islamic banks. The data sources that the author uses are primary data and secondary data. This research is classified as qualitative descriptive research, meaning that this research attempts to describe, record, analyze and interpret what is researched through observation, interviews and studying documentation. This research is field research or field research. Field research is research carried out on an event that actually happened. The strategy of sharia banks to maximize customer growth in the city of Parepare is not very optimal because there has not been much outreach to the public about sharia banks, so the public still equates sharia banks with general (conventional) banks. Keywords: Syariah Bank, general (conventional) banks